2008
DOI: 10.4049/jimmunol.181.8.5720
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 Inhibits Osteoclastogenesis Indirectly through Lymphocytes and Is Required for the Maintenance of Bone Mass in Mice

Abstract: IL-23 stimulates the differentiation and function of the Th17 subset of CD4+ T cells and plays a critical role in chronic inflammation. The IL-23 receptor-encoding gene is also an inflammatory disease susceptibility gene. IL-23 shares a common subunit with IL-12, a T cell-dependent osteoclast formation inhibitor, and we found that IL-23 also dose-dependently inhibited osteoclastogenesis in a CD4+ T lymphocyte-dependent manner. When sufficiently enriched, γδ T cells also mediated IL-23 inhibition. Like IL-12, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 45 publications
4
82
0
Order By: Relevance
“…In the latter model IL-23 was necessary for induction of lung fibrosis by transforming growth factor ␤. There is evidence that IL-23 might have a different effect under inflammatory conditions versus noninflammatory conditions: it can mediate bonedestructive processes (32,33) and is found within inflammatory lesions in the gut mucosa of patients with Crohn's disease (34), but also induces increased bone mass under noninflammatory conditions (35). We and others have hypothesized that new bone formation starts from fibrous tissue and that the development of fibrous tissue is crucial in AS (4,13,14).…”
Section: Il-23 In the Spine Of Patients With Asmentioning
confidence: 99%
“…In the latter model IL-23 was necessary for induction of lung fibrosis by transforming growth factor ␤. There is evidence that IL-23 might have a different effect under inflammatory conditions versus noninflammatory conditions: it can mediate bonedestructive processes (32,33) and is found within inflammatory lesions in the gut mucosa of patients with Crohn's disease (34), but also induces increased bone mass under noninflammatory conditions (35). We and others have hypothesized that new bone formation starts from fibrous tissue and that the development of fibrous tissue is crucial in AS (4,13,14).…”
Section: Il-23 In the Spine Of Patients With Asmentioning
confidence: 99%
“…IFN-c is the leading cytokine expressed by TH1 lymphocytes TH1 cells and has important functions in host defence. Interestingly, also the major differentiation signal for TH1 cells, IL-12 inhibits osteoclastogenesis [46]. The suppressive function of IFN-c on osteoclast differentiation is based on interference with RANKL signalling, where IFN-c constitutes a negative feedback loop for RANKL-mediated osteoclast activation [52].…”
Section: Interferons (Ifn)mentioning
confidence: 99%
“…Both inhibitory and stimulatory roles of IL-23 on osteoclastogenesis through T cells were reported. Quinn et al reported that IL-23 inhibited osteoclast formation from mouse spleen cells in CD4 + T-and γδT celldependent mechanism (Quinn et al, 2008). Mice lacking a subunit of IL-23 (IL-23p19 defi ciency) represented reduced bone mass phenotype, supporting the role of IL-23 in limiting bone resorption in resting conditions.…”
Section: Regulation Of Osteoclast Differentiation By Interleukins Thamentioning
confidence: 93%